TATA KELOLA PERUSAHAAN DAN PENGUNGKAPAN RISIKO KEUANGAN PADA PERUSAHAAN KEUANGAN - Suharto, AKM Bambang; Siregar, Nolita Yeni (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2021)
The purpose of this study is to empirically examine the effect of Good Corporate Governance on disclosure of financial risk in financial companies. Good corporate governant variables used in this study are the size of the board of commissioners, the number of board meetings, the composition of independent commissioners, the number of audit committee meetings, and the composition of the independent audit committee. The sample in this study used 66 of financial companies listed at Indonesia Stock Exchange (BEI) for 2015-2017, with 198 obervation. The sampling technique using purposive sampling method. The result of this study are size of the board of commissioners and the composition of independent commissioners have a positive significant effect on risk disclosure.